Electrification of irrigation in Bangladesh: addressing energy access, groundwater sustainability, and food security - Banerjee, Anurag; Radhakrishna, Manikanta; Ray, Shreya; Sharma, Vinay; Kishore, Avinash; Varshney, Deepak; Chakraborty, Shreya (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2024)
This data note presents the energy-irrigation landscape in Bangladesh has undergone rapid transformation, particularly with the widespread adoption of electric pumps. This shift is marked by increased rural electrification, rising diesel prices, and new regulations on the electrification of pumps and groundwater use [e.g. the National Energy Policy; Ground Water Management Act, 2018]. These changes have significant implications for the informal groundwater markets, where the majority of farmers rely on it to gain access to irrigation facilities. Groundwater is the major source of irrigation in Bangladesh. These evolving dynamics in Bangladesh's energy-irrigation nexus underscore the critical need for integrated policies addressing sustainability, energy access, and food security. A holistic approach is imperative to navigate the complex interplay between energy, agriculture, and environmental sustainability, ensuring resilience and equitable resource access.